ENTAMOEBAGINGIVALIS FREQUENCY IN ORAL CAVITY - Pruneda G., Casas; Cruz M.,, Barron; Cardenas J., Mariel; Cantu F.J.,, Gutierrez; Rodriguez R., Oliva; Ramirez G.F., Romo; Lopez L.R., Gamez (European Scientific Journal, ESJ, 2014)
The parasite Entamoebagingivalis is a protozoan from the oral cavity of the human, primarily found in dental plaque which forms on the base of the gums, around and between the teeth and in gingival tissues. It has been studied because of their relationship with dental pathologies. Frequency of Entamoebagingivalis in soft dental plaque was studied in 80 samples from three populations with an age range of 4-66 years with a null mouthwash until three times a day. The first population was patients who came to the diagnostic clinic of the faculty of dentistry with a dental pathology such as caries and gingivitis in which a 18.4% frequency of protozoa was found, the second population were students of the Faculty of Chemistry with good oral hygiene in which Entamoebagingivaliswas found in 18.2%, and the third population of people was taken randomly from the town of Vanegas, San Luis PotosÃ, MÃ©xico where the frequency of Entamoebagingivalis was 5%. Were related variables such as sex and frequency of oral hygiene, without showing an association. In addition to the protozoan, the presence of some germs, such as fungi and bacteria were also found.